2015
DOI: 10.1126/science.aac5891
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and spectroscopy of the young jovian planet 51 Eri b with the Gemini Planet Imager

Abstract: Directly detecting thermal emission from young extrasolar planets allows measurement of their atmospheric compositions and luminosities, which are influenced by their formation mechanisms. Using the Gemini Planet Imager, we discovered a planet orbiting the ~20-million-year-old star 51 Eridani at a projected separation of 13 astronomical units. Near-infrared observations show a spectrum with strong methane and water-vapor absorption. Modeling of the spectra and photometry yields a luminosity (normalized by the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
407
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(421 citation statements)
references
References 83 publications
12
407
2
Order By: Relevance
“…8, the gray lines and shaded regions indicate synthetic planets that have a luminosity compatible with measurements of two important directly imaged extrasolar planets at 20 Myr, namely β Pictoris b (Lagrange et al 2009 and 51 Eridani b (Macintosh et al 2015). Both stars are members of the β Pic moving group with an age estimate of 21 ± 4 Myr (Binks & Jeffries 2014), while Macintosh et al (2015) adopt 20 ± 6 Myr for 51 Eri. It is interesting to study the properties of the synthetic analogs of the two planets, but it should be kept in mind that we only selected them based on a compatible luminosity.…”
Section: Comparison With β Pic B and 51 Eri Bmentioning
confidence: 99%
See 1 more Smart Citation
“…8, the gray lines and shaded regions indicate synthetic planets that have a luminosity compatible with measurements of two important directly imaged extrasolar planets at 20 Myr, namely β Pictoris b (Lagrange et al 2009 and 51 Eridani b (Macintosh et al 2015). Both stars are members of the β Pic moving group with an age estimate of 21 ± 4 Myr (Binks & Jeffries 2014), while Macintosh et al (2015) adopt 20 ± 6 Myr for 51 Eri. It is interesting to study the properties of the synthetic analogs of the two planets, but it should be kept in mind that we only selected them based on a compatible luminosity.…”
Section: Comparison With β Pic B and 51 Eri Bmentioning
confidence: 99%
“…Direct imaging discoveries include the well-studied β Pic b ) and HR 8799 bcde objects (Marois et al 2008(Marois et al , 2010, but also a handful of exciting recent additions: HD 95086 b and 51 Eri b with small lower mass limits of a few Jupiter masses, and HIP 65426 b (Rameau et al 2013a,c;De Rosa et al 2016;Macintosh et al 2015;Samland et al 2017;Chauvin et al 2017). As advances both in observational and data-reduction techniques make it possible to probe closer in to the host stars, one could expect an increasing number of discoveries N if the radial-velocity result that dN/dP ≈ −0.7 < 0 (Cumming et al 2008), derived for masses M = 0.3-10 M and periods P = 2-2000 days, holds also at separations relevant for direct imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The Gemini instrument launched a multiyear search for Jupiter-like planets orbiting hot, young stars in November 2014. Early observations of 51 Eridani, a 20-million-year-old star about 30 parsecs away, spotted a Jupiter-like world 2.5 times farther from the star than Jupiter is from the Sun 10 . The spectrum showed that this exoplanet, dubbed 51 Eridani b, has an atmosphere containing more methane -a known component of Jupiter's atmosphere -than any other exoplanet.…”
Section: Spectrum C Dmentioning
confidence: 99%
“…With present-day instrumentation, this technique is mostly limited to young self-luminous giant planets in very long-period orbits ( 10 AU) around nearby young stars (e.g., Macintosh et al 2015). The next generation of exoplanet imaging efforts on the ground and in space will target long-period, mature Jovian planets similar to GJ 676A b (Traub et al 2016;Kasper 2015) and will pave the path towards observing the spectrum of a potential Earth-twin, which will require a large space observatory.…”
Section: Prospects For Directly Imaging the Gas Giants Around Gj 676amentioning
confidence: 99%